Manifest destiny (2013), volume 5 ebook Mnemophobia & chronophobia. - Dingess, Chris (Manifest Destiny (2013), 2018)
Lewis and Clark hunker down for the winter, and all is calm.until old enemies emerge from the fog. As their fortified walls are overrun, the Corps of Discovery have a front-row seat to the American Dream gone mad. Collects MANIFEST DESTINY #25-30. Author: Chris Dingess. Illustrator: Matthew Roberts . 2017 Ministry of Trouble, Inc. .